Angiospermic Flora of Bethuadahari Reserve Forest, Nadia (india) - Das, A. P.; Lahir, A. K. (Indian Forester, 1990)
Betbuadahari reserve is a 121 hectare man-made deer sanctuary. A recent floristic survey in this forest recorded 193 species of angiosperms covering 51 dicotyledonous and 11 monocotyledonous families of which 49.2% are herbs. 11.9% climbers, 124% shrubs and 26.4% are trees, 23 species of plants were found to grow only within the grazing free fenced area. Out of 52 species of trees atleast 24 are basically introduced. Polyalthia suherosa Benth is the dominant shrub in the under-storey and in open areas Vitex negundo L, Lantana camara L. Chromolaena odorata (L) King et Robia and Glycomis arborea L.) DC. are common. The poor representation of Chamaephytes, Hemicryptophytes and Cryptophytes are due to the excessive pressure of grazing. Altogether 90 species were seen to be eaten by deer of which 35 species are of very good fodder value. Necessary measures to improve the structure of its vegetation, fodder content and beauty has been suggested.